THE CURRENT STATE OF THE GREIG TULIP (TULIPA GREIGII Regel) IN NATURAL CONDITIONS AND IN CULTIVATION IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses studies of natural populations of the Greig tulip (Tulipa greigiiRegel). Separate foci with different colors of petals - yellow and orange - were found in the Toktogul basin and in the Shamshy tract. Work has been carried out on the cultivation of this specieswith bulbs and seeds in various high-altitude zones in the Chui Valley. Research work in this direction continues.
Keywords: Greig's tulip, population, bulbs, seeds, cultivation